THE EFFECT OF DEEP BACK MASSAGE TECHNIQUE IN DECREASING MUSCULAR PAIN AMONG PRIMIPARA MOTHER IN KASSI-KASSI HEALTH CENTRE MAKASSAR - rosita rosita (Stikes Graha Edukasi Makassar, 2020)
Introduction: Labor pain can be caused by increased fetal pressure and amnionic fluid in the lower segment of the uterus and cervix that cause the flow of blood and oxygen to the placenta disrupted. There are some types of efforts to decrease childbirth pain such as pharmacology and non pharmacology and one of them is deep back massage. It can decrease pain by inhibiting pain signals and increasing flow and oxygen throughout the body. To determine the effect of deep back massage techniques on the reduction of first stage labor pain in primipara mothers in the working area of Kassi-Kassi Health Center Makassar.. Method: The research design used quasi experiment one-group pretest-posttest design by involving one object group. This group was pain observed (Visual Analog Scale) before intervention. Then, it was observed pain again after the intervention (20 minutes with a frequency of 20-30 times) in childbirth mothers. Results: The results of the research indicate that of the 16 respondents who gave birth from August to September, 15 respondents (83.8%) have unbearable pain and 1 of them (6.2%) has severe pain. Meanwhile, after having deep back massage, 13 respondents (81.2%) have moderate pain, and 3 of them (18.8%) have severe pain. The result of Wilcoxon test indicates (p=0.000) value meaning that p value is <0.05. Conclusion: There is an influence of deep back massage technique on the reduction of first stage labor pain in primipara mothers in the working area of ??Kassi-Kassi Health Center Makassar.